Penggunaan Okokan Pada Tawur Kasanga (Perspektif Pendidikan Sosio Religius) - I Made Yoga Sedana; Made Sri Putri Purnamawati; Ngakan Ketut Juni (Jayapangus Press, 2019)
This research was conducted based on researchers' interest in a religious ritual on the use of Okokan on Tawur Kasanga in the Kediri Traditional Village, Kediri District, Tabanan Regency. Religious rituals on the use of Okokan on Tawur Kasanga in the Kediri Traditional Village, Kediri District, Tabanan Regency are unique rituals in the Kediri Traditional Village. The sound of this musical instrument Okokan is believed to provide fibration so that it can neutralize negative forces. This study was examined from a socio-religious perspective referring to the concept of Tri Hita Karana. Problems that will be discussed in this study are 1. Procession of the implementation of ritual use of Okokan on Tawur Kasanga in Kediri Traditional Village, 2. The function of using okokan as a means of Tawur Kasanga in Kediri Traditional Village, 3. The value of socio-religious education contained in the use of Okokan on Tawur Kasanga in Kediri Traditional Village. The purpose of this study is to find out and understand the procession, function and value of education in the socio-religious perspective through the ritual of using okokan on tawur kasanga. The theory used in this study is religious theory and value theory from Koentjaraningrat and functional structural theory from Tri Guna. This type of research uses qualitative research. Data collection techniques in this study are observation, interviews, literature studies and documentation. The technique of presenting the analysis in this study by using description analysis. The results of the discussion of this study are (1) the procession of the implementation of the ritual use Okokan on Tawur Kasanga begins with preparation, then the implementation of the okokan staging and ends with the laying okokan in each banjar Kediri Traditional Village (2) The function of using Okokan as a means of Tawur Kasanga is a religious function, complementary function in Tawur Kasanga ceremony, function of neutralizing negative forces, function of cultural preservation, aesthetic function, harmony function. (3) Value of socio-religious education contained in the use of Okokan on Tawur Kasanga, Parhayangan value, Pawongan value, and Palemahan value.